Mechanical behavior of biomaterials - Davim, J. Paulo (Woodhead Publishing, 2019)
Mechanical Behaviour of Biomaterials focuses on the interface between engineering and medicine, where new insights into engineering aspects will prove to be extremely useful in their relation to the biomedical sciences and their applications. The book's main objective focuses on the mechanical behavior of biomaterials, covering key aspects, such as mechanical properties, characterization and performance. Particular emphasis is given to fatigue, creep and wear, fracture, and stress and strain relationships in biomaterials. Chapters look at both experimental and theoretical results. Readers will find this to be an essential reference for academics, biomechanical researchers, medical doctors, biologists, chemists, physicists, mechanical, biomedical and materials engineers and industrial professionals.
Keywords: Biomechanics.; Biomedical engineering.; Biomedical materials.; elektronické knihy; electronic books